Acetaminophen use during pregnancy and offspring attention deficit hyperactivity disorder – a longitudinal sibling control study. Issue 2 (22nd June 2021) - Gustavson, Kristin; Ystrom, Eivind; Ask, Helga; Ask Torvik, Fartein; Hornig, Mady; Susser, Ezra; Lipkin, W. Ian; Lupattelli, Angela; Stoltenberg, Camilla; Magnus, Per; Mjaaland, Siri; Askeland, Ragna Bugge; et al.
Abstract: Background: Maternal acetaminophen use during pregnancy is associated with increased risk of ADHD in the child. This could reflect causal influence of acetaminophen on fetal neurodevelopment or could be due to confounding factors. The aim of the current study was to examine unmeasured familial confounding factors of this association. Methods: We used data from 26, 613 children from 12, 902 families participating in the prospective Norwegian Mother, Father, and Child Cohort Study (MoBa). The MoBa was linked to the Norwegian Medical Birth Register and the Norwegian Patient Registry. Siblings discordant for prenatal acetaminophen exposure were compared regarding risk of having an ADHD diagnosis. Results: Children exposed to acetaminophen up to 28 days during pregnancy did not have increased risk of receiving an ADHD diagnosis compared to unexposed children. The adjusted Hazard ratio (aHR) was 0.87 (95% C.I. = 0.70‐1.08) for exposure 1 to 7 days, and 1.13 (95% C.I. = 0.82–1.49) for 8–28 days. Long‐term exposure (29 days or more) was associated with a two‐fold increase in risk of ADHD diagnosis (aHR = 2.02, 95% C.I = 1.17–3.25). In the sibling control model, the association between long‐term acetaminophen use and ADHD in the child was aHR = 2.77 (95% C.I. = 1.48–5.05) at the between‐family level, and aHR = 1.06 (95% C.I. = 0.51–2.05) at the within‐family level. Conclusions: Both the exposed and the unexposed children of mothers with long‐term use of acetaminophen in one of the pregnancies had increased risk of receiving an ADHD diagnosis. This indicates that the observed association between long‐term acetaminophen use during pregnancy and ADHD in the child may at least partly be confounded by unobserved family factors.